Psychoanalysis of Characters in the Novel Assalamualaikum Baitullah by Asma Nadia: Study of Literary Psychology - Yeni Puspitasari Puspitasari; Marista Dwi Rahmayantis; Andri Pitoyo (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the personality structure of the characters in Asma Nadia’s novel Assalamualaikum Baitullah based on Sigmund Freud’s psychoanalytic theory, which includes the id, ego, and superego. This novel was chosen because it presents the complex psychological dynamics of the characters through life conflicts, trauma, loss, and the process of searching for the meaning of life and spirituality. The study uses a literary psychology approach with a qualitative descriptive method. The data source is Asma Nadia’s novel Assalamualaikum Baitullah, while the research data consist of words, phrases, sentences, dialogues, and character actions that reflect aspects of the id, ego, and superego. Data collection techniques were carried out through reading and note-taking, while data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results showed that 80 data were found, consisting of 12 data aspects of the id, 40 data aspects of the ego, and 28 data aspects of the superego. The id aspects include instincts, death instincts, and anxiety instincts. The ego aspect includes repression, sublimation, projection, displacement, rationalization, regression, aggression, apathy, and fantasy and stereotypes. The superego aspect includes guilt, suppressed guilt, self-punishment, shame, sadness, hatred, and love. Research findings indicate that the ego aspect is the most dominant personality structure, so that characters in the novel tend to face conflict through considerations of reality and defense mechanisms.